Wire array Z-pinch experiments at Imperial College - Lebedev,SV; Ampleford,DJ; Bland,SN; Bott,S; Chittenden,JP; Jennings,C; Haines,MG; Rapley,J; Palmer,JBA (2004)
The physics of plasma formation in wire array Z-pinches and effects of the radial redistribution of mass by the precursor plasma flow were studied in experiments on the Magpie generator (1MA, 250ns). Scaling of the ablation rate of the wires with global magnetic field and wire number, and importance of the material left behind by the implosion are discussed.